Exploring extended scope of practice in dietetics: A systems approach. Issue 4 (11th May 2016) - Ryan, Dominique; Pelly, Fiona; Purcell, Elizabeth
Abstract : Aim: The aim of this study was to explore health professionals' perceptions of an extended scope of a practice clinic, and develop a framework using a systems approach to facilitate extended scope models across various health settings. Methods: A qualitative investigation using semi‐structured interviews with four health professionals involved in an extended scope dietitian‐led gastroenterology clinic in a hospital in regional Queensland was conducted. A case study design was utilised to investigate interviewees' perceptions of the clinic. Participants were conveniently, purposively sampled. Transcript analysis involved a descriptive analytical approach. Interviewee responses were coded and categorised into themes, and investigator triangulation was used to ensure consistency between individual analyses. A secondary interpretative analysis was conducted where relationships between key themes were mapped to the Systems Engineering Initiative for Patient Safety work system model. Results: Interviewees identified various factors as vital inputs to the work system. These were categorised into the four key elements: stakeholder support, resources, planning and the dietitian. Clinic outcomes were categorised into the impact on four key groups: patients, the dietitian, the multidisciplinary team and the health system. Mapping of the relationships between inputs and outcomes resulted in an implementation framework for extended scope of practice. Conclusions: Extended scope of practice in dietetics may provide positive outcomes for various stakeholders. However, further development of extended scope roles for dietitians requires increased advocacy and support from governments, professional bodies, training institutions and dietitians. We have developed an implementation framework which can be utilised by health professionals interested in embracing an extended scope model of care.